Association between methylation potential and nutrient metabolism throughout the reproductive cycle of sows. Issue 3 (22nd March 2019) - van Riet, Miriam M. J.; Millet, Sam; Langendries, Karolien C. M.; van Zelst, Bertrand D.; Janssens, Geert P. J.
Abstract: DNA methylation is an important epigenetic strategy for embryo development and survival. The one‐carbon metabolism can be disturbed by inadequate provision of dietary methyl donors. Because of the continuous selection for larger litters, it is relevant to explore if highly prolific sows might encounter periods of methyl donor deficiency throughout their reproductive cycles. This study, therefore, assesses the fluctuation(s) in methylation potential (MP) and aims to link possible methyl donor deficiencies to nutrient metabolism. In total, 15 hybrid sows were followed from weaning of the previous reproductive cycle (d‐5) to weaning of the present cycle. Blood samples were taken at d‐5, 0, 21, 42, 63, 84 and d108 of gestation, the day of parturition (d115), two weeks of lactation (d129) and at weaning (d143). Blood plasma samples were analysed for S‐adenosylmethionine (SAM), S‐adenosylhomocysteine (SAH), free methionine, free glycine, acetylcarnitine and 3‐hydroxybutyrylcarnitine. Serum samples were analysed for urea and creatinine. Generally, MP (i.e. ratio SAM:SAH) increased throughout gestation ( p  = 0.009), but strongly fluctuated in the period around parturition and weaning. From d108 to parturition, absolute plasma levels of SAM ( p  < 0.001), SAH ( p  = 0.031) and methionine ( p  = 0.001) increased. The first two weeks of lactation were characterised by an increase in MP ( p  = 0.039) due to a remaining high value of SAM and a distinct decrease in SAH ( p  = 0.008). During the last two weeks of lactation, MP decreased ( p  = 0.038) due to a decrease in SAM ( p  < 0.001) and a stable value for SAH. The methylation reactions seem to continue after weaning, a period crucial for the follicular and embryonic development of the subsequent litter. This study thus demonstrates that the methylation status fluctuates substantially throughout a sow's reproductive cycle, and further research is needed to identify the factors affecting methylation status.